2021
DOI: 10.3390/bs11080113
|View full text |Cite
|
Sign up to set email alerts
|

Social and Mental Health Impact of Nuclear Disaster in Survivors: A Narrative Review

Abstract: This narrative review synthesizes the literature on the psychological consequences of the Three Mile Island nuclear accident of 1979, the Chernobyl nuclear disaster of 1986, and the Fukushima nuclear disaster of 2011. A search was conducted on OVID for studies in English from 1966 to 2020. Fifty-nine studies were included. Living through a nuclear disaster is associated with higher levels of PTSD, depression, and anxiety. Decontamination workers, those living in closest proximity to the reactor, and evacuees e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 74 publications
(251 reference statements)
0
5
0
3
Order By: Relevance
“…In addition, food and water supply was a concern especially for mothers of young children [6]. In comparative studies between the accidents in Chernobyl and Fukushima, it has not been possible to identify any major differences in terms of mental health consequences [3,10], but following the Chernobyl accident, studies show that mental health impairment, e.g. depression and post-traumatic stress still persist elevated two decades later [11,12].…”
Section: Learning From Historymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, food and water supply was a concern especially for mothers of young children [6]. In comparative studies between the accidents in Chernobyl and Fukushima, it has not been possible to identify any major differences in terms of mental health consequences [3,10], but following the Chernobyl accident, studies show that mental health impairment, e.g. depression and post-traumatic stress still persist elevated two decades later [11,12].…”
Section: Learning From Historymentioning
confidence: 99%
“…After experiencing a nuclear disaster, the most common mental health disorders reported are PTSD, anxiety and depression [10]. PTSD can occur as a delayed or prolonged reaction to a traumatic event or situation of exceptionally threatening or catastrophic nature.…”
Section: Mental Health Consequences After Radiological or Nuclear Dis...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies found that exposure to a nuclear threat is associated with negative mental health outcomes. In reviewing the literature on three major nuclear accidents, the Three Mile Island nuclear accident in the United States (1979), the Chernobyl nuclear disaster in Ukraine (1986), and the Fukushima nuclear disaster in Japan (2011), there were higher levels of PTSD, anxiety, and depression among those who experienced one of those disasters compared to who were not exposed to such a threat [ 41 ]. The mental health impact of nuclear accidents is not limited to those directly affected.…”
Section: Discussionmentioning
confidence: 99%
“…Em revisão narrativa sobre saúde mental frente a desastres nucleares, verifica-se nível aumentado de sofrimento psicopatológico geral 13 . Sendo citado, como fatores de risco ao acometimento mental, a perda de familiares, amigos e de emprego e a necessidade de mudar-se de casa, angústia pelo isolamento 13 -aspecto cuja relevância será ainda mais expressiva no período pandêmico.…”
unclassified